Course Outline - Diploma in Shariah Legal Practice (DSLP) - Ali, Zuraidah (2021)
Diploma in Shariah Legal Practice (DSLP) is a postgraduate diploma programme that combines substantive and procedural knowledge with Syari’e legal practitioners and lawyers' advocacy skills in Malaysia. It was explicitly designed to produce skilled Shari'ah law practitioners who can understand, analyse, and solve problems related to Shari'ah law submitted by any party who needs their services.